Pengaruh Motivasi Kerja, Kepuasan Kerja dan Etos Kerja Terhadap Kinerja Karyawan di PT Surya Indah Food Multirasa Jombang - Mahirah, Auni Mahfud; Setiani, Setiani (Fakultas Syariah INSURI Ponorogo, 2022)
This study aims to examine and obtain information about: 1. The effect of employee motivation on employee performance, 2. The effect of job satisfaction on employee performance, 3. The effect of work ethic on employee performance, and 4. Simultaneous effect of work motivation, job satisfaction and ethos work on employee performance. This study uses a method with a quantitative approach and the instrument is a questionnaire. The object of this research is PT Surya Indah Food Multirasa Jombang with a total sample of 80 employees who are also respondents in this study. The analysis technique used is multiple linear regression analysis. By using the SPSS statistical test tool, the results of this study provide evidence that: 1. There is a positive and significant effect of employee work motivation on employee performance, 2. There is a positive and insignificant effect of job satisfaction on employee performance, 3. There is a positive and significant influence on ethos work on employee performance, and 4. Simultaneously there is a significant effect of work motivation, job satisfaction and work ethic on employee performance.